Power Aspects of the Tennessee Valley Authority's Program - Mason, Edward S. (Quarterly Journal of Economics, 1936)
I. The power program of the Authority may be treated independently of other objectives. — This program represents a new development in federal power policy, 378. — II. An analysis of the provisions of the Act relating to power, 379; constitutional limitations on a federal agency in the electricity field, 383; legislative limitations on the activities of the Authority in the Tennessee Valey area, 389. — III. Objectives of the Authority's power program, 393. — Significance of these objectives for the problem of cost calculation, 396. — The problem of investment allocation, 398. — The problem of the interest rate, 407. — The determination of the price of acquired properties, 410. — IV. Conclusions, 412.